NILAI TAMBAH DAN STRATEGI PEMASARAN KOPI BUBUK AROMA - Melisa Ayu Oktariza; Nusril Nusril; Ketut Sukiyono (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
The purpose of this study are (1) to know the value added resulting from the processing of coffee beans into ground coffee aroma. (2) to analyze what the marketing mix strategy that prioritized to increase the sales volume of ground coffee. (3) to know what the alternative marketing strategy that right of any marketing mix. The method used is the value-added method Hayami and analytical hierarchy process (AHP). The results showed that the value added obtained in this process for regular packaging amounted to 8.065 with value added ratio of 26,52%, while the value added to the plastic foil ratio amounted to 10.035 with an added value of 27,50 %. On this criterion that the first priority is the financial condition of the company with its weight amounted to 0.334 while the subcriteria most priority is the product strategy with a weight of 0.345. Capital is a priority of the most preferred in stretegi products with a weight of 0.667. then became a priority to the alternative product is mendeversifikasikan size product with a weight of 0.262.